1985
DOI: 10.1016/0022-4804(85)90096-4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of focal cerebral ischemia by cardiac output augmentation

Abstract: Intravascular volume expansion has been employed successfully for treatment of ischemic stroke from cerebral vasospasm and from cerebrovascular occlusive disease. The physiologic mechanism responsible for this success has not previously been delineated in controlled experimentation. The objective of this investigation was to delineate the effects of cardiac output and of hemodilution in a primate model of focal cerebral ischemia. Two groups of anesthetized rhesus monkeys received extensive cardiovascular monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In their study, Sinha et al found a strong correlation between the flow volume in the common carotid artery and the CO, and about 11 % of the CO was distributed to each common carotid artery. Other studies have also shown correlation between the carotid artery Doppler flow volume measurement and the CO [15,16].…”
Section: Discussionmentioning
confidence: 73%
“…In their study, Sinha et al found a strong correlation between the flow volume in the common carotid artery and the CO, and about 11 % of the CO was distributed to each common carotid artery. Other studies have also shown correlation between the carotid artery Doppler flow volume measurement and the CO [15,16].…”
Section: Discussionmentioning
confidence: 73%
“…Data in the literature on the correlation of cardiac output and CBF in these patients are controversial. Some authors described a passive association between HMV and CBF in primates 6,21 ; others failed to show a correlation in humans. 7 The disappointing results of an Austrian hemodilution stroke trial 22 should be discussed in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, patients were treated with a combination of hypervolemia, hemodilution, and induced hypertension ("triple-H therapy") to augment cerebral blood flow by increasing cerebral perfusion pressure and lowering blood viscosity [36][37][38]. However, as the various components of triple-H therapy were studied, the focus of therapy has shifted to euvolemic-induced hypertension.…”
Section: Hemodynamic Augmentationmentioning
confidence: 99%